Zina Dalam Kajian Teologis dan Sosiologis - Kisworo, Budi (Al-Istinbath: Jurnal Hukum Islam, 2016)
This paper aims to examine the meaning of adultery through the lens of the theological and sociological theory. Adultery is forbidden which has been condemned both by religion and by the positive law in Indonesia, although the meaning of adultery in the religious sense and the positive law has a different sense, but still have the same meaning in substance. The data presented in this paper comes from the study of literature by searching for sources that are directly related to the theme. This study found that to have adultery sometimes not known by public because it is done in secret. In such circumstances, adultery is still personal sin, and Allah still provides an opportunity for each executant to immediately repent. By contrast, if it is already known by public, then the act has an effect on social life so that it became a social sin. It is not enough to repentance only, but it must be given sanctions against the perpetrators. Keywords: Adultery, Theological theory, Sociological theory